2019
DOI: 10.3892/mmr.2019.10278
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic protection of matrine and lycopene against lipopolysaccharide‑induced acute lung injury in mice

Abstract: Acute lung injury (ALI) is a major cause of morbidity and mortality globally, and is characterized by widespread inflammation in the lungs. Increased production of reactive oxygen species is hypothesized to be associated with ALI. Matrine and lycopene are active products present in traditional Chinese medicine. Matrine is an effective inhibitor of inflammation, whereas lycopene decreases lipid peroxidation. Therefore, it was hypothesized that combinatorial treatment with matrine and lycopene may provide synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 41 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…In a non-tumorigenic human skin keratinocytes (HaCaT) model, MT combined with acitretin negatively regulates the phosphorylation of PI3K/Akt/mTOR signaling pathway, and plays a synergistic role in inducing autophagy and cell cycle G0/G1 phase arrest ( Jiang W. W. et al, 2019 ). Studies have shown that the combination of MT and lycopene possessed a synergistic protective effect on a LPS-induced acute lung injury (ALI) mouse model through the inhibition of the NF-κB pathway ( Li W.W. et al., 2019 ). Rong et al.…”
Section: Drug-drug Interactions Of Mtmentioning
confidence: 99%
“…In a non-tumorigenic human skin keratinocytes (HaCaT) model, MT combined with acitretin negatively regulates the phosphorylation of PI3K/Akt/mTOR signaling pathway, and plays a synergistic role in inducing autophagy and cell cycle G0/G1 phase arrest ( Jiang W. W. et al, 2019 ). Studies have shown that the combination of MT and lycopene possessed a synergistic protective effect on a LPS-induced acute lung injury (ALI) mouse model through the inhibition of the NF-κB pathway ( Li W.W. et al., 2019 ). Rong et al.…”
Section: Drug-drug Interactions Of Mtmentioning
confidence: 99%
“…In a murine model (C57BL/6 mice) for emphysema, lycopene administration lessened the detrimental effects of chronic cigarette smoke exposure [42]. Lycopene treatment was found to ease LPS-induced acute lung injury (ALI) in murine animal models [46], BALB/c mice, and LPSinduced ALI in a rat model [47]. Lycopene extracted from tomatoes could reduce the burden of lung fibrosis's pathological effects in a rodent study [52].…”
Section: Discussionmentioning
confidence: 99%
“…One method of generating ALI in these animals was through the administration of lipopolysaccharide (LPS). One study investigated the synergistic protective efficacy of lycopene and matrine, an alkaloid found in kinds of Sophora plants, against LPS-induced ALI compared to the corticosteroid dexamethasone (DEX) in BALB/c mice [46]. Mice were intraperitoneally injected with DEX (5 mg/kg BW), matrine (25 mg/kg BW), lycopene (100 mg/kg BW), or a combination of the matrine + lycopene treatments for seven days before a final dosage of LPS (5 mg/kg BW).…”
Section: Acute Lung Injurymentioning
confidence: 99%
“…Matrine (tetracycloquinolizindine) ( Li W. W. et al, 2019 ), antidesmone (tetrahydroquinoline) ( Lu et al, 2017 ), cepharanthine (bisbenzylisoquinoline) ( Huang et al, 2014 ), epigoitrin (pyrrolidine) ( Luo et al, 2019 ), isotetrandrine (bisbenzyltetrahydroisoquinoline) ( Liang et al, 2014 ), neferine (bisbenzylisoquinline) ( Zhao et al, 2010 ), and oxysophoridine (quinolizidine) ( Fu et al, 2015 ) are other alkaloids that have shown anti-lung injury effects evaluated by in vivo and in vitro experiments. Accordingly, they regulated the proinflammation mediators and oxidative markers ( Table 1 ).…”
Section: Phytochemicals As Potential Agents For Coronavirus-associatementioning
confidence: 99%